1997
DOI: 10.1007/s002130050218
|View full text |Cite
|
Sign up to set email alerts
|

Isolation impairs place preference conditioning to morphine but not aversive learning in mice

Abstract: Morphine (8-100 mg/kg IP) induces place preference conditioning in mice. The effect of two different periods of isolation (15 and 30 days) was examined. Mice isolated for 15 days but not 30 days exhibited place preference conditioning to morphine (8 mg/kg). After 30 days of isolation morphine could not induce place preference conditioning with the following doses (8, 16, 64, 100 mg/kg). Social regrouping of male mice previously isolated for 30 days with naive female mice for 15 or 30 days resulted in a reappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
5
30
0
3
Order By: Relevance
“…To measure CPP, we used a two-compartment box made of grid and bar floors, respectively, which were previously selected on the basis of the absence of immediate spontaneous preference for the mice (Coudereau et al 1997). In this study, we confirmed the absence of immediate preference or aversion for one of the two floors (Table 1).…”
Section: Conditioned Place Preference Induced By Morphine and Dopaminmentioning
confidence: 96%
See 1 more Smart Citation
“…To measure CPP, we used a two-compartment box made of grid and bar floors, respectively, which were previously selected on the basis of the absence of immediate spontaneous preference for the mice (Coudereau et al 1997). In this study, we confirmed the absence of immediate preference or aversion for one of the two floors (Table 1).…”
Section: Conditioned Place Preference Induced By Morphine and Dopaminmentioning
confidence: 96%
“…The procedure has been extensively described (Coudereau et al 1997). The place conditioning apparatus consisted of several identical grey Plexiglas boxes (15 cm×30 cm×40 cm high) consisting in two compartments (15 cm×15 cm each) with distinctive textures: "grid" floors were composed of a brass wire (1 mm thickness) lozenged mesh with holes of 10×5 mm, "bars" floors were made of parallel bars (diameter 3 mm) 8 mm apart.…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…For example, rats reared in social isolation are somewhat less sensitive than social housed rats to the rewarding effects of heroin and morphine in conditioned place preference procedures (Coudereau et al 1997;Schenk et al 1983;Wongwitdecha and Marsden 1996) but self-administer heroin more readily (Bozarth et al 1989). Concerning environmental enrichment, Bardo and colleagues found that rats reared in EE show increased conditioned place preference to morphine than rats housed in social isolation (Bardo et al 1997), whereas another study found no differences in conditioned place preference to morphine between enriched and isolated rats (Smith et al 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Da mesma forma, o acondicionamento de apenas um animal por gaiola após o desmame, induz significativas alterações no comportamento adulto (Einon e Morgan, 1977;Jones et al, 1989). Alterações na reatividade emocional de roedores causadas pelo isolamento social têm reflexos na atividade locomotora (Gentsch et al, 1988;Wilkinson et al, 1994;Domeney e Feldon, 1998), defecação (Holson et al, 1991, neofobia (Hall et al, 1997a, b), aumento dos comportamentos agressivos em relação a co-específicos (Wongwitdecha e Marsden, 1996), aumento dos comportamentos agressivos ao serem manipulados (Hatch et al, 1963), no condicionamento de preferência a lugares (Coudereau et al, 1997), na inibição pré-pulso ("pre-pulse inhibition") (Day-Wilson et al, 2006), no condicionamento clássico aversivo ao contexto (Rudy, 1996;Coudereau et al, 1997) e na memória espacial (Pacteau et al, 1989). Não surpreende, portanto, que ratos socialmente isolados vêm sendo utilizados como modelo para o estudo da ansiedade (Parker e Morinan, 1986) e da neofobia.…”
Section: Memória De Reconhecimento Social E Interferência De Rotinas unclassified
“…Por outro lado, é possível que a manutenção dos animais agrupados antes do primeiro encontro social tenha contribuído para a memória de reconhecimento social de longa duração. De fato, a literatura da área inclui relatos de que animais mantidos isolados exibem comprometimento no desempenho em testes de memória (Gentsch et al, 1988;Wilkinson et al, 1994;Rudy, 1996;Wongwitdecha e Marsden, 1996a,b,c;Coudereau et al, 1997;Coventry et al, 1997;. Essa questão permanece sem resposta, mas poderia ser facilmente examinada experimentalmente, submetendo-se co-específicos a diferentes períodos de isolamento social antes dos testes.…”
Section: Discussão Geral E Conclusõesunclassified